Prenatal Detection of a Case of Proximal Femoral Focal Deficiency (PFFD) - (:unkn) unknown (KOWSAR PUBL, 2009)
Proximal femoral focal deficiency (PFFD) is a developmental disorder of the proximal segment of the femur and acetabulum, resulting in shortening of the affected limb and impairment of the function. It is a spectrum of congenital osseous anomalies characterized by a deficiency in the structure of the proximal femur. It is a sporadic disorder with an increased incidence in infants of diabetic mothers. Abnormality ranges from aplasia/hypoplasia of the entire femur to complete absence of the proximal end. The disorder is more commonly unilateral and is apparent at birth; however, bilateral involvement is also rarely seen.
Keywords: Proximal Femoral Focal Deficiency (PFFD); Anomaly; Prenatal; Sonography